PERBEDAAN KEMANDIRIAN BELAJAR SISWA DITINJAU DARI POLA ASUH ORANG TUA DAN IMPLIKASI DALAM LAYANAN BIMBINGAN DAN KONSELING (DESKRIPTIF KUANTITATIF PADA SISWA KELAS X & XI DI SMA NEGERI 6 PANDEGLANG) - fitri fatiroh; Vasco Delano; Devi Nurul Fikriyani (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the differences in students’ learning independence based on parental parenting styles at SMA Negeri 6 Pandeglang. The background of this research stems from the importance of parenting in shaping children’s character and learning attitudes, especially during adolescence when students are expected to be independent in managing their own learning process. The sample consisted of 88 students from grades X and XI, selected using purposive sampling techniques. Data were collected through questionnaires containing instruments on learning independence and parenting styles, then analyzed using the Analysis of Variance (ANOVA) statistical method. The results showed significant differences in learning independence based on parenting styles, with an F value of 38.28 and a significance level of 0.00 < 0.05. Students with democratic parenting had the highest learning independence, followed by permissive, while the lowest was found in authoritarian parenting. These findings indicate that parenting style significantly influences the development of students’ learning independence. The implications of this study provide a foundation for guidance and counseling services to design programs that support the improvement of students’ learning independence in a structured and sustainable manner.